Health Mate - Israa Issa; Yaser kharouf (My University, 2025)
The project describes how an integrated mobile application was designed and developed to encourage healthy behaviors through individual health monitoring. Users can monitor their daily wellness and health targets by tracking food intake along with calorie control and physical activity and sleep patterns and water consumption. The notification system sends users immediate alerts for three main activities: drinking water and eating meals and scheduled exercise sessions. The application offers its services to two different types of users who include regular users and nutritionists. The app enables users to store their health records while allowing nutritionists to view their patient files which helps them evaluate progress and perform observations along with providing consultative support. Users can utilize the AI-powered food recognition feature to monitor food items which tracks food consumption and calorie content with high accuracy through advanced technology and user-friendly QR code scanning. The application provides a straightforward interface that users and nutritionists can access through different login methods to use customized health tracking instruments; Users can log their daily food intake. Additionally, the app includes a log of exercise, water consumption, and sleep patterns. One of the most important features of the "Health Mate" is its advanced notification system, which sends reminders about water consumption and diet schedules. This allows nutritionists to use the app to monitor their clients' progress by integrating AI technologies with smart tracking. This paper documents the design and development process, system architecture, key functions, and test and analysis results of the Health Mate, demonstrating its effectiveness in supporting health management and professional nutrition guidance. The Health Mate app is a comprehensive health monitoring application that focuses on users' overall well-being and changes in their health habits and also covers the following areas: 1. Raising awareness of nutrition and health Track the consumption of different groups of nutrients such as proteins, carbohydrates, fats, and vitamins Food items are recognized by the use of QR codes and AI in the food quality screening process. 2. Promoting healthful behaviors Reminder system: Notifications to take medication, drink water, and organize workouts Sleep tracking: to improve your sleep quality, track sleep stages of deep, light, and REM What is done while exercising is exercise logging - the calculation of movements and burned calories. 3. Assisting with nutritionist follow-up to monitor health problems, register yourself as a user or a nutritionist Log virtual meetings and give personalized dietary advice to the user. 4. Integration and ease of use An interface that is easy enough for even children to operate and understand, the fitness app you are using can be paired with your fitness tracker (such as Apple Watch or Fitbit). 5. Added value to society: Fighting obesity and chronic diseases (such as diabetes) by the means of nutritional awareness, Health care cost saving by using smart remote monitoring.